Perceptions of preschool teachers and parents about the role of children observers in peer violence - Kojić, Miroslava; Markov, Zagorka; Kojić Grandić, Smiljana (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Peer violence impacts the development of children who are victims of violence, but children who witness violence are also prone to experience consequences pertaining to their ​​socio-emotional development. The state should provide dedicated support to intervention programmes in preschool institutions aimed at preventing and suppressing peer violence, which would focus on children who are witnesses, i.e., observers of violence. Objectives. This research was aimed at analysing the perceptions of preschool teachers and parents about the role of children observers in peer violence. Methods. The sample consisted of preschool teachers employed in preschool institutions in several cities in Serbia (n = 104) and parents whose children attended preschools (n = 84). For the purposes of the research, an adapted Likert-type scale was used, which assessed the role of children “observers” of peer violence and the possibilities of developing support programmes for children exposed to violence. The instrument was developed based on a pilot study on the role of children observers in bullying. Results. Research results showed that the perceptions of parents pertaining to the role of children observers in peer violence were statistically significantly different in relation to the opinions of preschool teachers. Parents believed that children who were observers of peer violence were not sufficiently involved in intervention programmes for the prevention and suppression of peer violence in preschool institutions. Conclusion. These findings have significant practical implications for the planning of initiatives in preschool institutions aimed at fostering a supportive environment in which children who witness peer violence would play a prominent role.